2013
DOI: 10.1080/08927014.2012.760125
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vibration frequency and amplitude on biofouling deterrence

Abstract: The use of vibration is proposed as a means of controlling the settlement of marine fouling organisms. In this study, panels with embedded lead zirconate titanate, known as PZT, were placed in the field over 3 months. The panels were vibrated at different velocity levels at frequencies between 70 and 445 Hz. It was found that barnacles (Amphibalanus variegatus Darwin and Elminius sp.) were the only fouling organisms affected by the applied vibration, and these organisms settled in significantly lower numbers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Preparation of coupon Watson et al [2014] and longer term fouling assemblages by Choi et al Choi et al [2013]. After the exposure period the coupon was photographed and then air dried for 7 days prior to storing at -18…”
Section: The Test Surfacementioning
confidence: 99%
“…Preparation of coupon Watson et al [2014] and longer term fouling assemblages by Choi et al Choi et al [2013]. After the exposure period the coupon was photographed and then air dried for 7 days prior to storing at -18…”
Section: The Test Surfacementioning
confidence: 99%
“…In subsequent trials, however, other researchers have not observed this antifouling efficiency at these low frequencies (Fischer et al, 1984;Choi et al, 2013). In sea trials, Choi et al (2013) investigated the effect of low frequency (70-445 Hz) vibration on biofouling. In contrast to Branscomb and Rittschof, no effect was observed, compared to a control, for frequencies below 200 Hz.…”
Section: Audio Frequency Range Studiesmentioning
confidence: 97%
“…3. Transducers used have included piezoelectric transducers (Branscomb and Rittschof, 1984;Choi et al, 2013;Gavand et al, 2007;Kitamura et al, 1995;Seth et al, 2010Guo et al, 2011a,b, 2012Mazue et al, 2011) and strips/films (Latour and Murphy, 1981;Murphy and Latour, 1979;Wooden and Edelman, 1981), magnetostrictive transducers (Sheherbakov et al, 1974), and audio speakers (Piper, 1977).…”
Section: Ultrasonic and Audio Biofouling Hardwarementioning
confidence: 98%
See 1 more Smart Citation
“…This is a unique study of its kind, is considered as the use of ultrasound and the concentration of 2.5 mg / ml of the active compound (Oleandrin) and were compared between the two separately, and in other studies used different frequencies of ultrasound (70 to 445 Hz), the Water basins contain on the larvae. It was observed to increase the vibration amplitude and a decrease in the number of marine barnacles conjoined at the frequency of 260 Hertz (18) (19) . Table 2: Effect of mixed ultrasound and oleandrin extract on the growth of cyprid barnacles B.a.amphitrite (the total number of larvae = 12).…”
Section: Effect Of Mixed Ultrasound and Oleandrinmentioning
confidence: 99%